Adaptive technologies in student-centered training of future engineers-teachers - Bakatanova, V. (Problems of Engineer-Pedagogical Education, 2021)
Features of using adaptive technologies in the process of student-centered training of future engineers-teachers are covered in article. The conducted bibliographic analysis revealed that the adaptive social and pedagogical system demands the relevant adaptive management. Respectively, the purpose of the work consisted in developing an algorithm of carrying out student-centered training by means of adaptive technologies. According to the purpose of the article, an algorithm of carrying out student-centered training of students of engineering and pedagogical specialties by means of adaptive technologies was developed and presented in a graphic form. A survey was conducted in order to find out what students thought of student-centered training at UEPA in the 2019/2020 academic year. The results of the survey demonstrated that all the students considered student-centered training to be an organic continuation and improvement of the educational process. Further work enabled students to create their own qualimetrical model of professional activity of the engineer-teacher. Implementation of the algorithm of student-centered training on the basis of involving students into the process of quality insurance of educational services at all stages as well as student-friendly forms of training and teaching methods, interactivity, mobility and mentoring helped made students’ requirements and expectations in regard to their own education adequate. The author drew a valid conclusion that the algorithm of carrying out student-centered training of future engineers-teachers by means of adaptive technologies, which contains five interconnected stages, allows conducting student-centered training more selectively, considering requirements and individual characteristics of students and also possibilities of the corresponding higher education institution. The perspective direction of further research in this regard is studying psychological peculiarities of adapting to student-centered training of students of both the sphere of technical training and the sphere of vocational pedagogical education.